Co-Deposition Mechanisms of Calcium Sulfate and Calcium Carbonate Scale in Produced Water - Yan Yan; Tao Yu; Huan Zhang; Jiayu Song; Chengtun Qu; Jinling Li; Bo Yang (Crystals, 2021)
Co-precipitation of mineral-based salts during scaling remains poorly understood and thermodynamically undefined within the water industry. This study focuses on investigating calcium carbonate and calcium sulfate mixed precipitation in scaling. Scaling is often observed in the produced water supply as a result of treatment processes. Co-precipitation results were compared with experimental results of a single salt crystallization. Several parameters were carefully monitored, including the electrical conductivity, pH value, crystal morphology and crystal form. The existence of the calcium carbonate scale in the mixed system encourages the loose calcium sulfate scale to become more tightly packed. The mixed scale was firmly adhered to the beaker, and the adhesion of the co-deposition product was located between the pure calcium sulfate scale and the pure calcium carbonate scale. The crystalline form of calcium sulfate was gypsum in both pure material deposition and mixed deposition, while the calcium carbonate scale was stable in calcite form in the pure material deposition. In the co-deposition, apart from calcite form, some calcium carbonate scale crystals had metastable vaterite form. This indicated that the presence of SO42− ions reduced the energy barrier of the calcium carbonate scale and hindered its transformation from a vaterite form to a calcite one, and the increase in HCO3− content inhibited the formation of calcium sulfate scale.